Analisis Pengaruh Distribusi Pendapatan Terhadap Kesejahteraan Masyarakat Dengan Inflasi Sebagai Variabel Intervening Di Desa Margamulya Kabupaten Lebak, Banten - Nunuk Triwahyuningtyas; Subur Subur; Sri Murtatik (Universitas Mercu Buana, 2019)
Society’s welfare is the ending purpose of each implemented policies by government. The measurement of society welfare will vary between countries based on the size of the country, the amount of people, and generated income in particular period. The welfare status in the territory of Margamulya, Lebak Banten might be felt unfair by some people because the welfare measurement one people does not only depend on the individual income after deducting expenses but also be subject to the satisfaction feeling of the income accepted. This research is conducted to acknowledge whether the income distribution affects social welfare directly through inflation as the intervening variable. The result indicated the direct influence of 0.380 and indirect 7.301 resulting in the total impact of 2.774. The test of intervening variable of inflation using the VAF method resulted 19.21%, depicting that if the effect is <20% then the inflation has almost no effect on social welfare. Therefore, the income distribution through overall income disparity exposed the value under 1 meaning the income distribution is not equal in the Margamulya Village, thus this is the dominant factor of the social welfare level.